FORMATION OF AESTHETIC CULTURE OF PRESCHOOL CHILDREN - Umarova G. A. (Galaxy International Interdisciplinary Research Journal, 2022)
The article describes in detail the importance of the formation of the aesthetic culture of preschool children in the educational process and beyond, teaching them to creative activities, the formation of the first elements of the aesthetic worldview, effective ways to implement it.Organizational and methodological recommendations on the aesthetic education of preschool children, the theoretical and pedagogical basis of their creative activity and its application in practice are intended for teachers, educators and methodologists working in this field.